Time of Planting and Nutrient Management for Off Season Production of Chinese Potato - ANJU, V.S. (JOURNAL OF ROOT CROPS, 2016)
Chinese potato (Plectranthus rotundifolius) is a minor tuber crop, the tubers of which are used as vegetable. Chinese potato is a season bound crop. The released varieties of Chinese potato namely SreeDhara from Central Tuber Crops Research Institute (CTCRI), Thiruvananthapuram and Nidhi from Regional Agricultural Research Station (KAU), Pattambi are recommended for planting during July-October (KAU, 2011). There is a great scope for off season production of Chinese potato using photo-insensitive varieties. The tubers fetch a higher price in the market due to great demand during off season. Kerala Agricultural University (KAU) has released one photo-insensitive variety namely Suphala in 2006. Hence an investigation was undertaken at College of Agriculture, Vellayani to fix the ideal time of planting and optimum nutrient management practices for exploiting the yield potential of the var. Suphala during the off season. The field experiment was conducted from November 2013 to May 2014. available P (35.2kg ha-1) and low in available N (213.26kg ha-1) and K (102kg ha-1) contents. The treatments consisted of four dates of planting (November 15, December 1, December 15 and January1) and three nutrient management practices(Recommended dose - 60:60:100 kg NPK ha -1 through fertilizers ;recommended dose through organic manures - 6 t FYM + 3 t coir pith compost + 3 t wood ash ha-1+ PGPR mix1 and Modified nutrient dose - 60:30:120 kg NPK ha -1 through fertilizers).